Glycemic Status and its effect on outcome of neonatal sepsis in a tertiary care hospital in Nepal - Chaudhary, Nanda Kishwor; Shrestha, Soni; Chaudhary, Suryakant; Khanal, Dikchhya; Chaudhary, Jyoti Kumari (Nepal Mediciti Medical Journal, 2024)
BACKGROUND Neonatal sepsis is a clinical syndrome characterized by signs and symptoms of infection with or without accompanying bacteremia in the first month of life. Neonatal sepsis is one of the leading causes of hospital admissions and neonatal deaths. Glucose remains the major source of energy for neonates and neonate’s brain is largely dependent upon glucose. Altered blood glucose level is common in neonatal sepsis. Both high and low blood glucose level is found to have significant negative impact on outcome of neonatal sepsis and is associated with high mortality. Altered blood glucose level is common in neonatal sepsis. AIMS This study aimed to determine the effect of glycemic status on outcome of neonatal sepsis in terms of mortality and duration of hospital stay. METHODS A prospective observational study was performed over a period of one year in 91 neonates admitted with diagnosis of neonatal sepsis in Neonatal Intermediate Care Unit (NIMCU) and Neonatal Intensive Care Unit (NICU) of Kanti Children’s Hospital who fulfilled the inclusion criteria. Random blood glucose was sent along with other investigations while performing septic screening before infusing intravenous fluids or other medications. These neonates were followed in NIMCU or NICU and immediate outcome and duration of hospital admission were recorded. Statistical analysis was done using SPSS 23. RESULTS Of total 91 neonates included in the study, altered glycemic status was present in 15% cases with hypoglycemia in 12% cases and hyperglycemia in 3% cases. Mortality among hypoglycemic neonates was high (9%) in comparison to normoglycemic neonates (4%) but the difference in mortality among these two groups was not statistically significant (p-value=0.44). Mortality among hyperglycemic neonates was significantly high (33%) in comparison to normoglycemic neonates (4%), which is statistically significant (p value=0.02). The median length of hospital admission among normoglycemic, hypoglycemic and hyperglycemic neonates was 7(3-21) days, 5(4-22) days and 5(5-9) days respectively, which is not statistically significant (p value=0.74) CONCLUSIONS Altered glycemic status is common in neonatal sepsis. Mortality is significantly high in septic neonates with hyperglycemia